First and Flourishing?: An Exploration of How First-Generation College Students Make Meaning of Their Well-Being Through Purpose, Relationships, and Multiple Identities. Issue 1 (2nd January 2022) - McCarron, Graziella Pagliarulo
ABSTRACT: The complexities of the first-generation college student journey may change how these students experience well-being — both what contributes to and detracts from it. As such, this study was conducted to deepen understanding of first-generation college students' lived experiences in relation to their well-being. This work shares findings from an interpretive, constructivist qualitative study grounded in interviews with 11 undergraduate, first-generation college students at a large, public, four-year institution in the Mid-Atlantic. Findings underscore connections between students' well-being and their goals, their on/off campus relationships, and their multiple identities. Implications for supporting first-generation college students' well-being are discussed.